Tocilizumab modulates the activity of the classical and alternative complement pathways in rheumatoid arthritis patients - Ferraz-Amaro, Iván; Santos-Concepción, Sergio; Castro-Hernández, Javier; Hernández-Hernández, Maria Vanesa; Tejera Segura, Beatriz; Luna, Cristina; Delgado-Frias, Esmeralda; Díaz-González, Federico (Frontiers in Immunology, 2025)
BackgroundTocilizumab (TCZ) is a monoclonal antibody that neutralizes interleukin (IL)-6 and is indicated for diseases characterized by markedly elevated inflammatory markers, such as rheumatoid arthritis (RA). The complement system has been implicated in the etiopathogenesis of RA.ObjectiveTo evaluate the effect of systemic IL-6 inhibition on complement pathways functional activity in RA patients treated with TCZ.DesingProspective non-interventional study.MethodsTwenty-seven RA patients included in the TOCRIVAR study who received TCZ (8mg/kg IV/q4w) were evaluated at baseline and at weeks 12, 24 and 52 of treatment. Disease activity, as assessed by composite indices, acute phase reactants, and new-generation functional assays of the three complement pathways, was evaluated at baseline and at each follow-up visit. Multivariable linear mixed models were used to determine changes in the complement system cascades over time.ResultsAfter adjustment for disease activity, basal levels of the classical and alternative pathways decreased significantly after TCZ treatment. The effect on the classical pathway remained significant after 52 weeks. The decrease in the alternative pathway was significant at weeks 12 and 24, but not at week 52 of TCZ treatment. TCZ had no effect on the lectin cascade throughout the follow-up.ConclusionTCZ reduces the activity of the classical and alternative pathways of the complement system in RA patients regardless of the improvement in disease activity. This finding may contribute to a better understanding of the mechanisms by which the IL-6 blockade reduces disease activity in RA patients.